2017
DOI: 10.3389/fmicb.2017.01620
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Analysis in Rats with Methamphetamine-Induced Conditioned Place Preference

Abstract: Methamphetamine abuse is a major public health crisis. Because accumulating evidence supports the hypothesis that the gut microbiota plays an important role in central nervous system (CNS) function, and research on the roles of the microbiome in CNS disorders holds conceivable promise for developing novel therapeutic avenues for treating CNS disorders, we sought to determine whether administration of methamphetamine leads to alterations in the intestinal microbiota. In this study, the gut microbiota profiles o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 52 publications
3
54
0
Order By: Relevance
“…The slowed GI motility disturbs the profiling of metabolites in the serum. In addition, heroin administration leads to an alteration in gut microbiota [ 36 ], and gut microbiota can in turn impact serum metabolites. Therefore, more well designed studies are needed to verify whether the observed changes in metabolites were caused by heroin reinforcement directly or were an indirect result mediated by gut motility/gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…The slowed GI motility disturbs the profiling of metabolites in the serum. In addition, heroin administration leads to an alteration in gut microbiota [ 36 ], and gut microbiota can in turn impact serum metabolites. Therefore, more well designed studies are needed to verify whether the observed changes in metabolites were caused by heroin reinforcement directly or were an indirect result mediated by gut motility/gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Although we have demonstrated that berberine facilitates the extinction of drug-associated behavior by enhancing consolidation of extinction memory, further studies are required to explore potential direct targets of berberine. A number of CNS diseases have been linked to abnormalities of gastrointestinal tract and recent studies suggest that gut microbiota plays a key role in the development of drug addiction (Kiraly et al, 2016;Ning et al, 2017;Meckel and Kiraly, 2019). Moreover, remarkable effects of berberine on gut microbiota and regulation of related disease pathophysiology have been recently reported (Cui et al, 2018;Feng et al, 2019;Yue et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al (2017) reported that Ruminococcus OTUs were more abundant in DU compared to HC [33]. Ning et al (2017) also found that Ruminococcaceae were more abundant in rats with methamphetamine-induced conditioned place preference than in the control group [34]. Furthermore, high abundance of Ruminococcaceae was reported to have a positive relationship with anxiety but was inversely correlated with place memory [62], which negatively impacts cognitive function [34].…”
Section: Discussionmentioning
confidence: 99%
“…Ning et al (2017) also found that Ruminococcaceae were more abundant in rats with methamphetamine-induced conditioned place preference than in the control group [34]. Furthermore, high abundance of Ruminococcaceae was reported to have a positive relationship with anxiety but was inversely correlated with place memory [62], which negatively impacts cognitive function [34]. Thus, the high abundance of Ruminococcus in the gut may be connected to impaired memory and cognitive function for DU subjects, although any relationship between Ruminococcus and cognitive function would require closer scrutiny using isolated strains in a model system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation